Living with Blindness - Westcott, Patsy (England Wayland Publishers, 1999)
Following the real-life experiences of blind children, this book helps readers discover the medical reasons behind blindness and how children cope with their condition. Readers are given an insight into the lives of young blind people and the ways in which they can help
Include Color Illustration and Index
Keywords: Blindness -- Blind